2022
DOI: 10.1002/ppsc.202200093
|View full text |Cite
|
Sign up to set email alerts
|

Gold Raspberry Shell Grown onto Nonspherical Lithium Niobate Nanoparticles for Second Harmonic Generation and Photothermal Applications

Abstract: They should also have a high photothermal conversion efficiency (percentage of absorbed light converted to heat), good photothermal stability, be nontoxic and allow for easy surface modifications. [2] The examples of PTAs found in the literature can be classified as noble metal-based nanoparticles (NPs), semiconductor nanocrystals, carbon-based NPs, and organic semiconducting polymeric NPs. [3] The noble metal PTAs, particularly the Au-based nanostructures are very attractive as Au has been extensively studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Au seeds were then grown, and the as-obtained raspberry-like Au nanoshells grown on LN NPs were thoroughly optimized and characterized. 25 As expected, broad plasmonic responses were demonstrated from the extinction spectra.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Au seeds were then grown, and the as-obtained raspberry-like Au nanoshells grown on LN NPs were thoroughly optimized and characterized. 25 As expected, broad plasmonic responses were demonstrated from the extinction spectra.…”
Section: Introductionsupporting
confidence: 72%
“…The first hyperpolarizability was shown to slightly decrease at high surface densities of Au nanoseeds for an almost constant depolarization ratio corresponding to the one of bare LN, thus evidencing the predominance of the core volume contribution. Au seeds were then grown, and the as-obtained raspberry-like Au nanoshells grown on LN NPs were thoroughly optimized and characterized . As expected, broad plasmonic responses were demonstrated from the extinction spectra.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The gold loading on LN NPs was also verified by EDS (Figure S2A), which confirmed increasing gold loading by varying the volume of AuSeeds suspension added to LN@BPEI (Figure S2A, inset). This was also supported by previously published XPS analysis . This work showed that upon BPEI coating followed by gold decoration, the presence of Au is observed in addition to an increase of C and N percentages, while Nb and O percentages decreased.…”
Section: Resultsmentioning
confidence: 98%
“…This was also supported by previously published XPS analysis. 25 This work showed that upon BPEI coating followed by gold decoration, the presence of Au is observed in addition to an increase of C and N percentages, while Nb and O percentages decreased. It was also noticed that the Au to Nb atomic ratio increased when the gold seeds to LN ratio increased, as expected.…”
Section: Characterization Of the Np Constructs (Ln Ln@ Bpei Auseeds A...mentioning
confidence: 99%